THE POWER OF MONEY IN PREMAN IN LOVE : A MARXIST APPROACH - Sugiharti, Sri (JURNAL DIMENSI, 2012)
Money has great rule in human life recently, even in the rural village such as Demolong in Wonosobo Regency that the head vilage roled by Marwoto cannot do anything because he was losen Raden Mas Pono who has much money. The theory of marxist used in research because it shows how the upper level (the have) is easily to oppress the lower level (the Poor). This research finds that money can cange the power of head village and love as well.